PENERAPAN STRATEGI REDIFINISI KONSTEKSTUAL UNTUK MENINGKATKAN PENGUASAAN KOSAKATA DAN AKTIVITAS PEMBELAJARAN - St. Nurbaya St. Nurbaya (LITERA, 2011)
applying a contextual learning strategy of redefinition in Indonesian. This was an action research study involving the students of Class VIII E of SMP Negeri I Seyegan, Sleman, Yogyakarta. The data were collected through observations, interviews, documents, and a vocabulary test. The research instruments included an interview guide, a checklist, and observation guide, and a vocabulary test. The data werequalitatively described. The results showed that the contextual redefinition strategy managed to improve the vocabulary mastery and learning activities. The students’ vocabulary mastery improved after each action cycle. The learning activities included raising questions, examining the correspondence between questions andlearning materials, using dictionaries to verify word meanings, having discussions,and constructing sentences to express contextual meanings.